Persepsi Anak Petani Terhadap Pekerjaan Sebagai Petani Di Kecamatan Tareran, Kabupaten Minahasa Selatan - Lumy, Angelique; Kaunang, Rine; Jocom, Sherly Gladys (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to describe the perceptions of farmers' children towards working as farmers in Tareran Sub-district, South Minahasa Regency. The method used was a survey with a quantitative descriptive approach. Samples were selected purposively, namely farmer's children aged 16-20 years from three villages with the highest population. Data were collected through questionnaires and analyzed using scoring method. The results showed that the perception of farmer children towards working as farmers was in the positive category. Internal factors, such as the potential for agricultural development in the local area, are the most valued aspects. Meanwhile, external factors such as the influence of family background tend to have a lower influence in shaping perceptions of the farming profession. These findings indicate that while the agricultural sector is still considered relevant, there are doubts about the long-term employment prospects of being a farmer. Therefore, educational approaches and policies that encourage the regeneration of young farmers by strengthening the image of the agricultural sector as a viable and sustainable profession are needed.